Prevalence of Antibody to Hepatitis C Virus in an Isolated Canadian Inuit Settlement. (1991) - Minuk, GY; Nicolle, LE; Gauthier, T; Brunka, J
Abstract : Sera from 720 inhabitants of Baker Lake, Northwest Territories, a community with high rates of hepatitis A and B infection, were tested for antibody to hepatitis C virus by commercial enzyme-linked immunosorbent assay. Only two individuals (0.3%) were positive, a 63-year-old female and an unrelated 10-year-old male. Neither individual was at increased risk of hepatitis C virus exposure. The results of this study indicate that hepatitis C virus infection is no more common in this northern Canadian Inuit settlement than it is in the blood donor population of southern Canada.